Wireless Sensor Networks Technology and Protocols - Matin, Mohammad A. (IntechOpen, 2012)
This book explores both the state-of-the-art and the latest developments in wireless sensor networks technology. It describes the fundamental concepts and practical aspects of wireless sensor networks and addresses challenges faced in their design, analysis and deployment. It is believed that the book will serve as a comprehensive reference for graduate and undergraduate senior students who seek to learn the latest developments in wireless sensor networks.